Deletion of the side chain assembly reveals diverse post-PKS modifications in the biosynthesis of ansatrienins. Issue 91 (16th September 2016) - Li, Xiaomei; Zhu, Jing; Shi, Guoyin; Sun, Mingwei; Guo, Zhixing; Wang, Haoxin; Lu, Chunhua; Shen, Yuemao
Abstract : Seven new ansatrienols were extracted from Streptomyces sp., and3 showed anti-T3SS activity, demonstrating diverse post-PKS modifications during ansatrienin biosynthesis. Abstract : Seven new ansatrienin-type ansamycins, namely, ansatrienols B–H (1–7 ), along with four known ones (8–11 ), were isolated from the strain Streptomyces sp. XZQH13OE ΔastC constructed by deleting the astC gene responsible for the assembly of the N -cyclohexanoyld -alanyl side chain. Their structures were determined by analysis of the 1D and 2D NMR spectroscopic data and high-resolution ESIMS. This study revealed the diverse post-PKS modifications during the biosynthesis of ansatrienins.